Phenotypic and genomic characterization of bacteriocin-producing lactic acid bacteria with probiotic and biotechnological potential for pathogen control in animal production - de Souza de Azevedo, Pamela Oliveira; de Medeiros Oliveira, Mauro [UNESP]; Kuniyoshi, Taís Mayumi; Matajira, Carlos Emilio Cabrera; Frota, Elionio Galvão; Dias, Meriellen; Bermúdez-Puga, Sebastián Armando; Pessoa, Amanda Romana Santos; Piazentin, Anna Carolina Meireles; Mendonça, Carlos Miguel Nóbrega; Pereira, Wellison Amorim; Converti, Attilio; et al. (Elsevier, 2025)
The emergence of antibiotic-resistant pathogens has raised significant concerns in the poultry industry, driving the search for alternatives to antibiotics as growth promoters in animal feed. Probiotics, particularly those belonging to the Lactic Acid Bacteria (LAB) group, represent a promising solution by mitigating the risk of infectious disease. However, a uniform concentration of probiotic LAB is not suitable for feed additives due to varying growth kinetics. Additionally, the genomic and physiological profiles of the LAB strains involved must be thoroughly evaluated. In this study, we provide an analytical framework to comprehensively assess LAB as potential antibiotic alternatives in poultry farming. Three LAB strains - Pediococcus pentosaceus (isolated from corn silage), Ligilactobacillus salivarius (from the poultry gut) and Lactococcus lactis (from the gut of rainbow trout) - were sequenced and characterized, with a focus on evaluating their probiotic potential and safety at the genomic level. The analyses included co-culturing LAB with pathogens, assessing viable cells, and determining the minimum inhibitory concentration of bacteriocin-like inhibitory substances (BLIS). In addition to demonstrating effective antimicrobial activity against avian pathogens (Salmonella spp., Clostridium spp. and Campylobacter coli), the results revealed notable probiotic traits in all three LAB strains, such as tolerance to bile salts and acidic environment and adhesion to intestinal cells. In conclusion, our analytical framework and results highlighted the potential of the tested LAB strains as biotechnological tools for developing zootechnical additives. These probiotics show promise as viable alternatives to antibiotics for enhancing poultry health and productivity.